Diferenças entre sexos na ativação muscular e estratégias motoras em atividade repetitiva e fadiga muscular no membro superior - Cid, Marina Machado (Universidade Federal de São Carlos, 2021)
The main objective of this PhD thesis was to evaluate sex differences in biomechanical exposure of the upper limb during the performance of low-level repetitive tasks. This research was based on four studies. The Study 1 consisted of a systematic review that aimed to synthesize evidence about sex differences in biomechanical exposure of upper limbs during low-level repetitive tasks. The systematic review included 24 studies and showed some sex differences in biomechanical exposure of upper limbs, such as a greater muscle activation in females during repetitive tasks, regardless of the presence of muscle fatigue or even a greater response to muscle fatigue induced by repetitive tasks showed by males, evidenced by kinematic changes in upper limb elevation. The quality of evidence level for these findings was classified as very low. In the Study 2, sex differences in the activity pattern of scapulothoracic muscles were evaluated during a low-level repetitive task performed with the upper limb positioned below shoulder level. Surface electromyography was recorded from all portions of the trapezius (upper trapezius - clavicular and acromial fibers, middle trapezius, lower trapezius) and serratus anterior. The initial and final periods of the task were considered for analyses. Females showed greater muscle activation for upper trapezius (acromial fibers) and serratus anterior muscles compared to men, regardless of task period. Sex differences were also evaluated considering postures of the upper body (Study 3) and muscle activity pattern of the neck/shoulder region (Study 4), during a low-level repetitive and fatiguing task, performed with the upper limb positioned above shoulder level. For these two studies, the pre- and post-fatigue periods were considered in the analyzes. In Study 3, postures of upper arm elevation and upper back, head and neck forward ﬂexion were evaluated using inclinometry. After muscle fatigue, there was a decrease in the upper arm elevation for both males and females, but with a greater decrease showed by males. In addition, females showed more non-neutral postures for head and neck than males, regardless of task period. In Study 4, surface electromyography was recorded from the same muscles evaluated in Study 2 and from anterior deltoid. The muscle activity variability of the anterior deltoid, expressed by the coefficient of variation (CV) of the electromyographic signal, increased after muscle fatigue, but only in males. In addition, females showed greater muscle activation and greater muscle activity variability (expressed by standard deviation and CV of the electromyographic signal) than males, regardless of task period. The results of this PhD thesis show sex differences in muscle activity pattern of neck/shoulder region and postures of the upper body during the performance of a repetitive task and that such differences are more evident when the task is performed with the upper limb positioned above shoulder level and in presence of muscle fatigue.
Sex differences in muscle activation and motor strategies during repetitive activity and muscle fatigue in the upper limb
Keywords: Fisioterapia; Ergonomia; Diferenças de gênero; Eletromiografia; Fadiga; Tarefa repetitiva; Pescoço/ombro; Cinemática; Inclinometria; Physical therapy; Ergonomics; Gender differences; Electromyography; Fatigue; Repetitive task; Neck/shoulder; Kinematics; Inclinometry; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL